Perancangan Alat Ukur Massa Jenis Zat Cair Menggunakan Cepat Rambat Gelombang Ultrasonik - Nanda Bagus Prawira; Abdul Rouf (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2018)
Density is a measure of the mass of volume unity. How to measure density in general by measuring the weight and dividing it by the volume of liquid, so in this way the measurement is not. Measurement of the density of the liquid based on the ultrasonic velocity becomes an alternative so that the measurement can be done directly, accurately, practically, and easily.Ultrasonic velocity becomes the variable to determine the density of the liquid. Time synchronization begins when the ultrasonic transmitter emits ultrasonic and is terminated when the receiver receives ultrasonic. The discrete ultrasonic wave transmission method is performed when the ultrasonic receiver receives transmittance from the ultrasonic transmitter then the 40KHz signal pulse is stopped and ultrasonic transmission is repeated up to 10 times the measurement data.From this study obtained some conclusions. Ultrasonic velocity is influenced by the viscosity of the liquid, ultrasonic velocity through 1394m / s aquades, ultrasonic velocity through cooking oil 1387m / s, ultrasonic velocity through liquid soap 1175m / s, ultrasonic velocity through liquid soap solution 40% 1317m / s , Ultrasonic velocity through liquid soap solution 70% 1257m / s, velocity measurement deviation of 0.43% and 0.01% density calculation type.